Implementation of Selective Policies on Foreign Doctor Practices in Indonesia - Irawan, Tri Pamungkas Ippilianingrum; Adriano, Adriano; Nugraheni, Ninis (Jurnal Indonesia Sosial Sains, 2025)
In many countries, especially those with a serious shortage of medical personnel, such as Indonesia, foreign doctors are essential to meet healthcare needs. This research examines the legal framework that allows foreign doctors to practice in Indonesia as well as the implementation of selective policies. This research utilizes normative, statutory, and conceptual approaches. This study found that there are no strict restrictions on the distribution of medical personnel in the foreign doctor legislation in Indonesia, as there are no regulations regarding the distribution of health workers in remote areas. Foreign doctors can only practice in Indonesia if there is a demand for health services, in accordance with Health Law No. 17 of 2023. Indonesia only allows foreign doctors who provide benefits to society, in accordance with its selective policy. The shortage of medical personnel in Indonesia is caused by the uneven distribution of doctors. Some communities, especially outside Java, lack access to professional doctors. Given the scarcity of specialist doctors in rural areas and the underdeveloped healthcare system in Indonesia, the placement of foreign doctors with specialized skills would be helpful.